Determinación del costo de producción de hortalizas de ciclo corto (zanahoria, remolacha, lechuga, cebolla blanca, rabano, frejol) en la asociación de productores agropecuarios la Vega del cantón Catamayo provincia de Loja, periodo abril - junio/2015 - Tapia Vega, María Del Cisne (2016)
It allowed to put into practice all the acquired and like that knowledge to increase them. In addition it allowed of “La Vega Association Producers’ ” to have a knowledge about the real cost of production of the different vegetables, was fulfilled by the aims raised, there decided the total cost of production and the unitary cost of the vegetables, of I design the different documents for the control the cost of elements. The record of the transactions of the accounting period was realized, the whole countable process developed, beginning with the initial inventory and finishing with four financial statements. There was calculated the unitary cost of every vegetable, every lettuce: 0,07 it sold at 0,20, ctvs., every plant of white onion: 0,08 and it sold at 0,10 ctvs., it frees of carrot: 0,1486 and one sold 0,15 ctvs., every pound of beet: 0,13 and one sold 0,15 ctvs., every plant of radish 0,05 and it sold at 0,083 ctvs. and every pound of bean: 0,33 and it sold at 0,50 ctvs., doing relation with the local market that would be Catamayo, the lettuce commercializes to an average price of 0,50, the plant of white onion to 0,10, the pound of carrot to a value of 0,30, the pound of beet 0,25, every plant of radish to 0, 08, the pound of bean to 0,50 and the regional market the prices are minor, the lettuce: 0,32, the white onion: 0,05, the pound of carrot: 0,20, the pound of beet: 0,13, every plant of radish: 0,05 and the pound of bean 0,35, prices that are not fixed. The result of the countable cycle was met loss of the exercise by a value of 92,75 dollars, this one is negative and it was given by the great quantity of agricultural equipment that they possess of the received donation and small production. One proceeded to elaborate the conclusions of the present work, and one gave recommendations to improve the functioning of the association and its results.